Functional and radiological outcomes of Essex-Lopresti procedure in intra-articular calcaneal fractures: a prospective study - Pareek, Varshant; Mishra, Ananya; Yadav, Mohit; Yadav, Kartik; Khandelwal, Deepak (International Journal of Research in Orthopaedics, 2025)
Background: Calcaneal fractures are among the most common tarsal bone injuries, often leading to significant morbidity. The Essex-Lopresti procedure is a minimally invasive surgical technique used to treat intra-articular fractures of the calcaneum. Objective of the study was to evaluate the functional and radiological outcomes of the Essex-Lopresti procedure in patients with intra-articular calcaneal fractures and assess post-operative pain relief and complication rates. Methods: A hospital-based prospective study was conducted at tertiary care centre, Jaipur, on 85 patients. Functional outcomes were assessed using the American Orthopaedic Foot and Ankle Society (AOFAS) score, while radiological outcomes were evaluated using Bohler’s angle. Results: The mean preoperative Bohler’s angle (15.19°) improved to 29.55° postoperatively and stabilized at 27.38° at the 6-month follow-up. The AOFAS score improved significantly from 47.56 preoperatively to 87.38 at 6 months. The mean Visual Analog Scale (VAS) score decreased from 7.53 preoperatively to 0.54 postoperatively, indicating significant pain relief. Conclusions: The Essex-Lopresti procedure is an effective treatment for intra-articular calcaneal fractures, achieving favorable functional and radiological outcomes with minimal complications.